Analysis Of Knowledge And Interest of Micro Business Actors In Sharia Business Loans PT. Sharia Pawn - Marina Zulfa; Ficha Melina; Boy Syamsul Bakhri; Nurul Muyasaroh (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2024)
Loans at Sharia Pawnshops for micro businesses are a solution to meet capital and economic needs without violating sharia principles. This institution is designed to apply the principles of sharia economics in financial services, especially in small business financing. Riba is prohibited in every transaction, and profits must be obtained in accordance with sharia law. Sharia Pawnshops also support zakat obligations and play a role in empowering micro businesses through halal and fair financing.  This study aims to analyze the level of knowledge and interest of micro business actors in sharia business loans at PT. Sharia Pawnshop. This study evaluates how the understanding of micro business actors regarding sharia principles and Islamic financial products offered by Sharia Pawnshops affects their interest in using this service. This research is quantitative descriptive with a sample of 100 micro business actors from the city of Pekanbaru.  The study found that there was a significant relationship between knowledge and interest in decision-making. This means that the more knowledge a person has about business and finance, the more likely they are to be interested in borrowing money at a sharia pawnshop.